2018
DOI: 10.1007/s00535-018-1500-0
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules and pancreatitis

Abstract: Acute and chronic pancreatitises are gastrointestinal inflammatory diseases, the incidence of which is increasing worldwide. Most (~ 80%) acute pancreatitis (AP) patients have mild disease, and about 20% have severe disease, which causes multiple organ failure and has a high mortality rate. Chronic pancreatitis (CP) is characterized by chronic inflammation and destruction of normal pancreatic parenchyma, which leads to loss of exocrine and endocrine tissues. Patients with CP also have a higher incidence of pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 86 publications
1
22
1
Order By: Relevance
“…The process is controlled by complex interactions between surface receptors on neutrophils and their corresponding endothelial cell ligands [18]. To further study the protective function of PEG35 in ANP, we focused on the expression of two of the main adhesion molecules involved in this inflammatory disease: P-selectin and Intercellular Adhesion Molecule-1 (ICAM-1) [19]. A significant up-regulation in both adhesion molecules was evident in the pancreas and lung three hours after ANP induction compared to control-operated mice ( Figure 4A,B).…”
Section: Peg35 Abrogated Anp-related Adhesion Molecules Expression Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is controlled by complex interactions between surface receptors on neutrophils and their corresponding endothelial cell ligands [18]. To further study the protective function of PEG35 in ANP, we focused on the expression of two of the main adhesion molecules involved in this inflammatory disease: P-selectin and Intercellular Adhesion Molecule-1 (ICAM-1) [19]. A significant up-regulation in both adhesion molecules was evident in the pancreas and lung three hours after ANP induction compared to control-operated mice ( Figure 4A,B).…”
Section: Peg35 Abrogated Anp-related Adhesion Molecules Expression Inmentioning
confidence: 99%
“…In recent years, several experimental studies have focused on the protective effects of PEGs. In lung endothelial cells, treatment with 15-20 kDa molecular weight PEG (PEG [15][16][17][18][19][20] was found to enhance cell function by activating endothelial cell-barrier signal transduction pathways and by contributing to cytoskeleton reorganization [8]. In addition, pre-treatment with PEG 15-20 in cultured ventricular myocytes subjected to hypoxia-reoxygenation reduced oxidative stress and apoptosis and increased cell survival [9].…”
Section: Introductionmentioning
confidence: 99%
“…β-Catenin, a type of transmembrane protein, is likely to play a crucial role in the progression and severity of AP [12]. Our previous research has determined that MSCs enhance the expression of β-catenin in SAP [20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that impaired autophagy has a crucial effect on the pathogenesis of SAP [ 9 11 ]. In addition, maintaining the normal action of adhesion molecules (such as β-catenin) and restricting their abnormal activation are beneficial in blocking the development of AP [ 12 ]. Therefore, investigations seeking to develop novel therapeutic tactics for SAP should concentrate on how to inhibit inflammatory responses, regulate autophagy, and maintain levels of adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that impaired autophagy has a crucial effect on the pathogenesis of SAP [9][10][11]. In addition, maintaining the normal action of adhesion molecules (such as β-catenin) and restricting their abnormal activation are bene cial in blocking the development of AP [12]. Therefore, investigations seeking to develop novel therapeutic tactics for SAP should concentrate on how to inhibit in ammatory responses, regulate autophagy and maintain levels of adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%